Shared Decision Making to Improve the Emergency Care of Older Adults: A Research Agenda. (25th November 2016) - Hogan, Teresita M.; Richmond, Natalie L.; Carpenter, Christopher R.; Biese, Kevin; Hwang, Ula; Shah, Manish N.; Escobedo, Marcus; Berman, Amy; Broder, Joshua S.; Platts‐Mills, Timothy F.
Abstract: Older emergency department patients have high rates of serious illness and injury, are at high risk for side effects and adverse events from treatments and diagnostic tests, and in many cases, have nuanced goals of care in which pursuing the most aggressive approach is not desired. Although some forms of shared decision making (SDM) are commonly practiced by emergency physicians caring for older adults, broader use of SDM in this setting is limited by a lack of knowledge of the types of patients and conditions for which SDM is most helpful and the approaches and tools that can best facilitate this process. We describe a research agenda to generate new knowledge to optimize the use of SDM during the emergency care of older adults.